Zoneamento ambiental da bacia do alto curso do rio Uberaba - MG como subsídio para gestão do recurso hídrico superficial - Abdala, Vera Lúcia (2005)
This work was developed in the drainage-basin from higher course of the Uberaba River, located in the county of Uberaba - Minas Gerais. This river, in all its extension from its water spring to the mouth of the Rio Grande River runs 140 kilometers. The environmental Protection Area (EPA) State Law 13183 (01/20/1999), is part of study that reaches an area of almost 53,500 hectares, marked among the geographical coordinates 19°30 and 19°45 south; and 47°38 and 48°00 west of Greenwich. The catchment area of water of the city of Uberaba is located in this space. They show an average flow of 1,200 liters per second and a legal flow by IGAM of 900 liters per second for the supply of the city. The aim of this research was to perform divisions of this area in environmental zones to subsidize future works concerned with the protection of the surface and underground sources of this drainagebasin. The analysis and perception of the landscape in this area was very important to understand the physical, social and economical factors that interfere in the quality and quantity of produced water in the area of study. This research was performed through data from a field survey for the characterization of the physical, social and economical aspects such as geology, salience, soil, the average flow of water and the use of soil, along with the use of topographical letter, satellite image and geomorphological maps. The obtained results were represented through a series of cartographic papers. The integration of these documents enabled a map of environmental zone of this area. Considering the analyses of the obtained information we can state that it is necessary to elaborate a handling plan to this area supported in three main parts: maintenance, restoration of the damaged areas and balanced use of its sources. This work is supposed to stimulate new researches involving this area of the Uberaba River, especially in the higher course, in order to study the issue more deeply.